Distinct microbially induced concrete corrosion at the tidal region of reinforced concrete sewers. (1st March 2019) - Song, Yarong; Tian, Yimei; Li, Xuan; Wei, Jing; Zhang, Haiya; Bond, Philip L.; Yuan, Zhiguo; Jiang, Guangming
Abstract: Microbially induced concrete corrosion (MICC) is a major deterioration affecting sewers worldwide. MICC is not uniform on sewer inner walls and often occurs at hot spots such as crown and tidal regions, which are critical to determine sewer service life. Especially, concrete corrosion in tidal regions is complicated due to the fluctuation of wastewater levels and the hydraulic scouring effects. The traditional methodology of corrosion monitoring also limits the study of the tidal corrosion. In this study, by using a combination of various advanced mineral analytical techniques and culture-independent 16S rRNA gene amplicon sequencing, the development of corrosion, the formation of corrosion products and the variation of microbial communities in tidal regions were investigated systematically. The physical-chemical characteristics in tidal regions varied with the distance from the wastewater surface. Above the wastewater, more severe corrosion was detected with a closer distance to wastewater, producing gypsum as the major corrosion products. The microbial succession in tidal regions occurred, with the coexistence of conventional autotrophic SOB and acidophilic heterotrophic bacteria initially, and shifting to the predominant colonization of Mycobacterium when pH reached around 1. The heterotrophic bacteria, i.e. Mycobacterium and Bacillus, were likely responsible for the observed corrosion due to the potential capability in generating sulfuric acid. The applications of advanced mineral and microbial analytical techniques were demonstrated effective in improving the understanding of concrete sewer corrosion. Graphical abstract: Highlights: A thorough investigation of concrete corrosion at tidal regions in sewers. Area right above wastewater is the most corrodible in gravity concrete sewer pipes. Concrete corrosion products characterized by mineral analytical techniques. Microbial structures vary with locations and evolve with time in tidal regions. Heterotrophic bacteria may be major contributors to corrosion at tidal regions.